Morphometry of Human Trachea in Male and Female using Computerized Tomography- A Comparative Study - Asad Ali Zardari, Pashmina Shaikh, Umbreen Bano, Mujeeb ur Rehman Sahito, Noor ul Ain Zardari, Shagufta Shaheen Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The architecture of the trachea can help doctors choose the right size of the endotracheal tube for patients. Non-invasive procedures like cadaveric dissection (CD) and Computed Tomography (CT) scans can also be used in the investigation. Objective: to describe the morphometry of a normal human trachea on CT scans and compare it to data from other studies Methodology: The normal CT scan pictures of 110 patients (69 males and 41 females) were analyzed in this prospective investigation. A 64-slice CT scanner was used to do chest CT scans. DICOM, a program for digital imaging and communication in medicine, was used to collect the data. For each parameter, the research population's lowest and maximum values were established. The correlation between all research variables and height and weight was determined using Pearson's correlation method. Height and weight were used as predictors in a regression analysis of substantially correlated factors. Results: In males, the AP and transverse diameters were substantially linked with height. The diameter of the AP and the CSA were found to be substantially linked with weight. A-P diameter, cross-sectional area, and volume were shown to be poorly predicted by weight. Weak predictors of length and transverse diameter were found to be height. In females, there was no association between height or weight with any of the research parameters. It was discovered that neither body mass index (BMI) nor height (or weight) could predict the dependent variables. Conclusion: The data might be valuable in the setup and design of tracheostomy tubes and endotracheal tubes in the future.